The Biophilic Architecture in Health Facilities for The Management Of Psychological Conditions of Asthma Patients - Apritasari, Yaseri Dahlia; Dheffanny, Dheffanny; Sembiring, Elsa Try Julita; Ravelino, Parlindungan (Department of Architecture Universitas Muhammadiyah Jakarta, 2025)
The increasing air pollution in Indonesia has raised concerns among the public, accompanied by a rise in respiratory diseases. One such disease requiring special attention is asthma, with a prevalence of 7%. Asthma is a chronic condition that can be potentially fatal if not properly managed, triggered by allergens and the psychological condition of the patient. Asthma management in Indonesia still needs improvement in terms of services and education, considering the psychological aspects. Thus, a biophilic architecture approach is needed to enhance the management of psychological aspects in asthma care. The research method involves qualitative and quantitative approaches with the following steps: (1) Synthesis of theory and observation of 10 hospitals with 14 biophilic architecture elements, (2) Collection of data on perceptions of implementing biophilic architecture elements in managing the psychological conditions of asthma patients with 41 respondents, (3) Identification of the management of psychological conditions of asthma patients with biophilic design, (4) Recommendations of biophilic design elements for the psychological healing of asthma patients. The results show that 12 out of 14 biophilic architecture elements are applied in the hospitals studied. Respondents' perceptions indicate that the psychological conditions of asthma patients that need to be managed are mainly dominated by overthinking, followed by anxiety, worry, and fear. Subsequently, biophilic design is derived from these findings to manage asthma patients' conditions by applying biophilic architecture elements in healthcare facilities. This research recommends the implementation of biophilic concepts in healthcare facility design to help manage the psychological conditions of asthma patients.